PENGARUH KEPUASAN GAJI, SISTEM PENGENDALIAN INTERNAL DAN BUDAYA ORGANISASI TERHADAP KECENDERUNGAN TINDAK KORUPSI - Ari Ani Dyah Setyoningrum (Universitas Boyolali, 2019)
Corruption becomes an important issue for countries in Asia including in Indonesia. The number of cases of corruption to make Indonesia as a nation with high levels of perceived corruption in the world. This study aimed to explore the perceptions of government officials at the State University in Central Java on the effect of pay satisfaction, internal control systems, and organizational culture against corruption tendencies. The sampling method using purposive sampling. The sample in this study amounted to 145 employees in the financial sub department of State University in Central Java. Data collection using questionnaire. Analysis of the data in this study using the Structural Equation Model ( SEM ) component -based Partial Least Square ( PLS ) 2.0 M3. The results of this study indicate that the variable pay satisfaction does not effect on the propensity to corruption. Internal control system does not affect the trend of corruption. Organizational culture collectivism dimension negatively affect the tendency of corruption. Organizational culture dimension uncertainty avoidance does not affect the trend in corruption. Keywords : corruption, pay satisfaction, internal control systems, organizational culture.